Pelatihan Pengolahan Produk Empon-empon Untuk Meningkatkan Pendapatan Masyarakat - Agus Susetyohadi; Mufti Alam Adha (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2021)
Agricultural products that are considered to have prospects are empon-empon. The types of empon-empon that have been produced by the farmers are temu comedy, white turmeric, yellow turmeric and ginger. Once the harvest season (usually June to December) a maximum of 200 tons fresh only for ginger and turmeric/yellow turmeric. This amount is based on market orders. The potential for these large empons needs special attention, because when sold in the form of fresh empons, the selling value is very low and the profits obtained are very small. For this reason, it is necessary to think about an effort to diversify products from these empon-empon materials by applying appropriate science and technology. This diversification is intended to find new types of products from empon-empon materials with standard quality qualities so that they have high competitiveness in the domestic market and export market. With this science and technology-based diversification, the market opportunity is getting bigger (increasing sales volume), higher selling value with much bigger profit. The choice to develop products from empon-empon raw materials is very appropriate. First, in terms of its function, apart from being a food flavoring agent, empon-empon is also an ingredient of herbal medicine to cure various diseases which are now in great demand.